People at Work : Life, Power, and Social Inclusion in the New Economy. - DeVault, Marjorie L., 1950- (NYU Press, 2008)
People at Work is noted sociologist Marjorie L. DeVault's groundbreaking collection of original essays on the complexities of the modern-day workplace. By focusing on the lived experiences of the worker, not as an automaton on an assembly line, but as an embodied human of flesh and bone, these essays offer important insight on the realities of the workplace, and their effects on life at home and in communities. With contributions from some of today's top scholars, each essay is a detailed case study of a different aspect of the working world. Compelling, lively, and sometimes chilling, the con.